Miras-e-Mohsin - Naqvi, Syed Mohsin (Lahore Mavra Publishers, 2007)
Syed Mohsin Naqvi ka tamam mazhabi kalam aik jild mein.
Urdu Poetry.
Keywords: Miras e Mohsin -- Meeras e Mohsin -- Syed Mohsin Naqvi -- Urdu Poetry -- Poetry - Urdu